A CRITICAL ANALYSIS OF THE POWER THEORIES OF FOUCAULT, BOURDIEU, AND HABERMAS IN THE CONTEXT OF HIGHER EDUCATION RESEARCH - Victor J. Pitsoe (Annals of the University of Craiova for Journalism, Communication and Management)
The article adopts three theoretical frameworks to explore the intricacies of "power." His discourse ethics contradict Habermas's belief in oppressive power. Free speech and ethical debates disregard power, contrary to Foucault's claim that the two are intrinsically related. Contrary to Foucault's insistence that power and history were inseparably linked, Habermas argued that one might seek truth apart from the other. There are two perspectives on power in Bourdieu's dialectical materialism